Lifetime modelling of high temperature corrosion processes : proceedings of an EFC Workshop 2001 - Schütze, Michael; Quadakkers, W. J.; Nicholls, J. R. 1948- (Book (Institute of Materials (Great Britain)), 2001)
The sections include papers on: alumina formers; iron oxide and chromia formers; composites and coatings; thermal barrier systems; and general lifetime prediction approaches.